Pengaruh Gaya Kepemimpinan Transformasional terhadap Keterikatan Kerja (Work Engagement) pada Guru dan Karyawan di Sekolah Menengah Atas - Andini, Adelia Navy Setyo; Ellyana Ilsan Eka Putri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Work Engagement refers to the extent to which individuals feel psychologically connected to their work. In organizational settings, transformational leadership is considered one of the factors that may influence this condition through inspiration, role modeling, and individual development. This study aimed to examine the relationship between transformational leadership and Work Engagement using a quantitative correlational approach involving 110 respondents. The instruments used were a transformational leadership scale (16 items) and a Work Engagement scale (9 items), both of which demonstrated satisfactory validity and reliability. Linear regression analysis revealed a significant positive relationship between transformational leadership and Work Engagement (p = 0.031), with a contribution of 4.3%. These findings indicate that better transformational leadership is associated with higher levels of Work Engagement, although other factors also play a role. Overall, this study emphasizes the importance of leadership in fostering Work Engagement within organizational contexts.